2001
DOI: 10.1046/j.1365-2249.2001.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

MC1 receptors are constitutively expressed on leucocyte subpopulations with antigen presenting and cytotoxic functions

Abstract: The expression of melanocortin MC(1) receptors on human peripheral lymphocyte subsets was analysed by flow cytometry using rabbit antibodies selective for the human MC(1) receptor and a panel of monoclonal antibodies against lymphocyte differentiation markers. The MC(1) receptor was found to be constitutively expressed on monocytes/macrophages, B-lymphocytes, natural killer (NK) cells and a subset of cytotoxic T-cells. Interestingly T-helper cells appeared to be essentially devoid of MC(1) receptors. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 28 publications
2
55
1
Order By: Relevance
“…However, the molecular mechanisms of these ␣-MSH anti-inflammatory effects have not been defined previously. MC 1 R is constitutively expressed in monocytes and subpopulations of lymphocytes and plays an important role in the anti-inflammatory action of ␣-MSH (19,39). Here, we found that PMA-treated THP-1 cells express significantly more MC 1 R when compared with Me 2 SOtreated HL-60 cells.…”
Section: ␣-Msh Inhibits Lps-induced Nf B Activation Via P38supporting
confidence: 50%
“…However, the molecular mechanisms of these ␣-MSH anti-inflammatory effects have not been defined previously. MC 1 R is constitutively expressed in monocytes and subpopulations of lymphocytes and plays an important role in the anti-inflammatory action of ␣-MSH (19,39). Here, we found that PMA-treated THP-1 cells express significantly more MC 1 R when compared with Me 2 SOtreated HL-60 cells.…”
Section: ␣-Msh Inhibits Lps-induced Nf B Activation Via P38supporting
confidence: 50%
“…How α-MSH treatment can lead to IRAK-M binding of IRAK-1 is not addressed by our findings, and how this can happen is complicated by the expression of three melanocortin receptors (MC1r, MC3r, and MC5r) that bind α-MSH on macrophages (Getting et al, 1999;Neumann Andersen et al, 2001;Taherzadeh et al, 1999). In general, the melanocortin receptors are G-protein coupled and are not evenly distributed throughout the body.…”
Section: Discussionmentioning
confidence: 83%
“…In general, the melanocortin receptors are G-protein coupled and are not evenly distributed throughout the body. The most predominate melanocortin receptor on macrophages and dendritic cells is MC1r (Neumann Andersen et al, 2001), although message for MC3r and MC5r can be detected (Taherzadeh et al, 1999). The engagement of α-MSH with MC1r elevates cAMP levels in the macrophages and activates a cAMP-dependent protein kinase A (PKA; Yoon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…MC1-R mRNA, but not protein, expression has been found on monocytes, B lymphocytes, NK cells, a subset of cytoxic T cells (4), dendritic cells (5), and more recently mast cells (6). MC1-Rmediated anti-inflammatory effects appear to occur via inhibition of NF-B activation (7,8) and protection of IB␣ degradation (9).…”
mentioning
confidence: 99%